Regression Of Hypertrophied Tonsil In Tonsillitis- A Case Report (Journal of Namibian Studies : History Politics Culture, 2023)
The current therapy for tonsillitis is surgical intervention, this case reports discuss the effective ayurvedic management of a case diagnosed as tonsillitis which was advised for tonsillectomy. After topical application, there is reduction in the size of tonsils, patient is asymptomatic and  free from recurrent attack of tonsillitis since 6 months. Hence safe method for reduction of enlarged tonsils.Case- A 11-year-old on allopathy treatment for a year was approached to our hospital with symptoms of pain while swallowing, hypertrophied tonsils, sore throat for the last 1 year. The features were suggestive of tonsillar hypertrophy has been assessed by Broadsky grading score. Diagnosed as Chronic Parenchymatous tonsillitis.Intervention- Topical application of Apamarga Kshara over the hypertrophied tonsilsResults- outcome of this case study revealed that there was reduction in the hypertrophied tonsils grade 2 to grade 1 in right tonsil and grade 3 to grade 1 in left tonsil according to the Broadsky grading score. There was no recurrence of symptom for last 6 monthsConclusion- Non-surgical intervention or topical application of Kshara of tonsillitis shows reduction in the size of tonsil, asymptomatic and no recurrence from 6 months.